Effect of microstructure evolution on tensile fracture behavior of Mg-2Zn-1Nd-0.6Zr alloy for biomedical applications. (15th November 2019) - Cai, Changhong; Song, Renbo; Wen, Erding; Wang, Yongjin; Li, Jingyuan
Abstract: The effect of microstructure evolution on tensile fracture behavior of biomedical Mg-2Zn-1Nd-0.6Zr alloy was investigated using OM, EPMA, SEM, TEM, EBSD and Nano-indentation. Results indicated that the as-cast Mg-2Zn-1Nd-0.6Zr alloy composed of α-Mg matrix, netlike and granular Mg35 Zn40 Nd25 (T3 ) secondary phases. Volume fraction of secondary phases in homogenized and solution-treated alloys decreased from 7.2% to 4.6% and 0%, respectively, whilst elements distributed more uniform and grain did not grow significantly. Grain size of extruded + aged alloy decreased from 110 μm to 12 μm, forming band-shaped phases with size of 0.2–1.5 μm and high-density nanoscale precipitates with size of 5–20 nm. Moreover, Mg35 Zn40 Nd25 phase exhibited higher elastic modulus (57.5 GPa) and hardness (1.47 GPa) than all matrices. With the change of phase content, phase morphology and grain size, the fracture mode of as-cast, homogenized, solution-treated and extruded + aged alloys during the conventional tensile test changed from intergranular fracture to quasi-cleavage fracture, transgranular fracture and ductile fracture. In addition, the effect of reduced surface integrity on cracking susceptibility could be ranked in the order of as-cast > homogenized > solution-treated > extruded + aged. Graphical abstract: Unlabelled Image Highlights: Microstructure evolution of biomedical Mg-2Zn-1Nd-0.6Zr alloy was studied by designing different fabrication process. Pre-immersed tensile test was designed to evaluate the tensile mechanical properties after a certain period of service. Elastic modulus, hardness and Volta potential of Mg35 Zn40 Nd25 (T3 ) phase were identified. Effect of corrosion-induced surface integrity on cracking susceptibility was investigated.